Sifat Fisik dan Keawetan Kayu Cemara Gunung (Casuarina junghuniana) di Pegunungan Bromo Kabupaten Probolinggo - Galit Gatut Prakosa; Tatag Muttaqin; Harjoko Harjoko (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2018)
Physical Characteristics and Durability of Cemara Gunung Wood (Casuarina junghuniana) in the Mt. Bromo Probolinggo. The purpose of this study is to find out the physical characteristics of Cemara Gunung wood and to know the durability of Cemara Gunung wood toward termite. The using methods knew the water content, density, and the development of wood thickness. Meanwhile, the selecting of wood durability test without the picking of using soil termites (Macrotermes gilvus) against the three wood samples by using (SNI) 01-7207-2014 regarding the durability of wood test towards wood-destroying organisms. The deriving results showed that the moisture content of the sapwood portion was more significant than the heartwood, based upon the highest density test on the heartwood, which was 1.24 g/cm3, the density of sapwood I and sapwood II was almost equal to 0.81-0, 82g/cm3. The higher the density value, the stronger the wood. The full development is directly proportional to density, the total development value of the two treatments is not too high due to hard Cemara Gunung wood. Based on the termite test showed the average weight reduction in the wood core test sample <3.52% (very resistant) class I. For testing sapwood, I and sapwood II (preservative) were not much different because it was included in the privileged class (3, 52-7,50) (class II). From the three trials of termite in bottles, the 15-day test (the bottle I) was the most effective followed by bottle II and bottle III.